Polyhydroxyalkanoate (PHA)-based electrospun nanofibers in environmental applications : Advances, limitations, and prospects - Al-Mutwalli, Sama A.; Taher, Mustafa N.; Ciftcioglu-Gozuacik, Bengisu; Koseoglu-Imer, Derya Y.; Lipnizki, Frank ; 0000-0002-3008-0182 (Journal of Environmental Chemical Engineering, 2025)
The increasing environmental crisis caused by plastic pollution, water contamination, and air pollution has driven the search for sustainable alternatives to conventional polymeric membranes. Polyhydroxyalkanoate (PHA)-based nanofiber membranes have emerged as biodegradable alternatives to conventional polymeric membranes, offering high porosity, tunable mechanical properties, and environmental compatibility. While numerous studies have explored PHA-based nanofiber membranes in biomedical and food packaging applications, up to the author knowledge, no comprehensive review has specifically addressed their potential for environmental applications. This manuscript fills this critical knowledge gap by providing a review of PHA-based nanofiber membranes for environmental remediation, focusing on water purification, air filtration, and antimicrobial treatments. The review highlights recent advancements in electrospinning techniques, polymer modifications, and functionalization strategies to enhance membrane performance for removing heavy metals, dyes, and oil from water while demonstrating high filtration efficiency for airborne particulate matter and aerosols. Additionally, it discusses the biodegradability of PHA membranes and their role in sustainable waste management. Despite their features, challenges such as high production costs, limited mechanical strength, and scalability issues remain key obstacles to commercialization. This review underscores the urgent need for further research to optimize production processes and expand the applicability of PHA-based nanofiber membranes in environmental sustainability. By bridging this knowledge gap, it provides a foundation for future advancements in eco-friendly membrane technology, paving the way for their real-world implementation in pollution control.
Publisher Copyright: © 2025 Elsevier Ltd.
Keywords: Air filtration; Biopolymer membranes; Electrospinning; Nanofiber membrane; Polyhydroxyalkanoate; Water/Wastewater treatment